In Deed : Certificates of Authenticity in Art - Hapgood, Susan; Lauf, Cornelia; Bellei, Veronica; De Kabinetten van de Vleeshal, Middelburg; Fondazione Bevilacqua la Masa, Venice; Khoj International Artists' Association, New Delhi; Mumbai Art Room, Mumbai; Nero HQ, Rome; John M. Flaxman Library Special Collections, the School of the Art Institute of Chicago, Chicago; The Drawing Center, New York; Salt Beyoglu, Istanbul (Amsterdam : Roma Publication, 2011)
Aubrecht, Ruben ; Barry, Judith ; Barry, Robert ; Brüggemann, Stefan ; Bhuta, Hemali ; Karle, Shreyas ; Bismuth, Pierre ; Boezem, Marinus ; Brecht, George ; Buren, Daniel et al.
In Deed : Certificates of Authenticity in Art, De Kabinetten van de Vleeshal, Middelburg, September 10 - October 9, 2011 / Fondazione Bevilacqua la Masa, Venice, October 14 - November 4, 2011 / Khoj International Artists' Association, New Delhi, November 18 - December 16, 2011 / Mumbai Art Room, Mumbai, January 13 - February 10, 2012 / Nero HQ, Rome, February 3 - March 2, 2012 / John M. Flaxman Library Special Collections, the School of the Art Institute of Chicago, Chicago, March 30 - April 28, 2012 / Salt Beyoglu, Istanbul, Spring 2012 / The Drawing Center, New York, Fall 2012
kunstcatalogus